Internationalization Process : Challenges of Dubai SMEs - Awale, Mohamud Hassan (2010)
The objective of this study is to explore the influential factors that contribute the successfulness of Dubai SME's to expand abroad by applying the theory of internationalization (OLI model), resource base theory, and institutional base theory. The internationalization process will be examined comprehensively to achieve the research objective by using the quantitative approach in the research. There are five main hypothesis has been developed to examine and analyze the progress of internationalization process of Dubai's SME's. Practically, the data of 93 small and medium sized enterprises from Dubai has been collected to review the actual condition of internationalization process in Dubai. Furthermore, data collected has analyzed with the SPSS software in obtaining the relevant information with numerical statistic and Pearson's correlation analysis.